Concerns about usage of smartphones in operating room and critical care scenario - Attri, JP (Medknow Publications & Media Pvt Ltd, 2016)
Smartphones and tablets have taken a central place in the lives of health care professionals. Their use has dramatically improved the communication and has become an important learning tool as the medical information can be assessed online at anytime. In critical care settings, use of smartphone facilitates quick passage of information through E-mail messaging and getting feedback from the concerned physician quickly, thereby reducing medical errors. However, in addition to the benefits offered, these devices have become a significant source of nosocomial infections, distraction for medical professionals and interfere with medical equipments. They may also put privacy and security of patients at stake. The benefits could be severely undermined if abuse and over use are not kept in check. This review article focuses on various applications of smartphones in healthcare practices, drawback of the use of these devices and the recommendations regarding the safe use of these devices.